Kilka uwag na temat recepcji twórczości Owidiusza w chrześcijańskeij poezji nowołacińskiej doby baroku - Milewska-Waźbińska, Barbara (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
In the Neo-Latin poetry written from the fifteenth to the eighteenth centuries, one can find numerous references to the works of Ovid. The aim of this article is to reflect on the ways works by the famous Roman poet were received in Neo-Latin Christian literature of the Baroque period. The article discusses three poetry cycles inspired especially by Ovid`s elegies. Ovidius Christianus, whose author is the Jesuit Laurent Le Brun, refers to the Bible and informs about the New World in the form of poetic letters. Ovidius Christianus by Johannes Baptista Bebber presents in the form of elegies the moral principles of Thomas à Kempis contained in his work De imitatione Christi. The third item described is the booklet Novum liber tristium, which contains a series of seven elegies dedicated to the sorrows of Our Lady. The author of the article tries to show how the works of Ovid influenced the poetic imagination of Christian authors.